Perlindungan Hukum Konsumen Terhadap Wanprestasi Dalam Transaksi E-Commerce di Indonesia - Putu Ayu Yukari Rantisari; I Gede Agus Kurniawan (Lembaga Teewan Journal Solutions, 2026)
The development of information technology has significantly encouraged the growth of electronic commerce (e-commerce) in Indonesia. The convenience of digital transactions has had a positive impact on national economic growth; however, it has also given rise to various legal issues, particularly concerning consumer protection. Breaches of contract, such as goods not matching their descriptions, delays in delivery, and online fraud, still frequently occur in e-commerce transactions. This study aims to analyze consumer legal protection against breaches of contract in electronic transactions as well as the responsibility of business actors in providing compensation to consumers. The research method used is normative legal research with statutory and conceptual approaches. The results of the study indicate that consumer legal protection has been regulated under the Consumer Protection Law, the Electronic Information and Transactions Law, and Government Regulations concerning Trade Through Electronic Systems. Nevertheless, the implementation of such legal protection still faces obstacles, including weak supervision, low public legal awareness, and difficulties in proving claims in digital transactions. Therefore, it is necessary to strengthen regulations and optimize supervision of marketplaces in order to create legal certainty for consumers.